Supervisi Kepala Madrasah Dalam Peningkatan Kinerja Guru: The Principal's Supervision in Enhancing Teacher Performance - Abdul Hamid (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2017)
The low quality of teacher performance remains a critical issue in many educational institutions, particularly at the elementary madrasah level, where academic supervision is often not implemented optimally. Based on the central role of the principal in achieving educational goals, this research aims to reveal how academic supervision is carried out to improve teacher performance. A qualitative approach was employed, using interviews, participant observation, and documentation at Madrasah Ibtidaiyah Sirajul Ulum, Probolinggo. The findings show that individual techniques such as orientation for new teachers, classroom observation, and individual conferences, as well as group techniques including teacher meetings, workshops, bulletin boards, and field trips, have been implemented but remain suboptimal. The main obstacles include the principal’s busy schedule due to external meetings and the lack of readiness among some teachers to be supervised. The study concludes that academic supervision has not yet run effectively and recommends routine, well-planned supervision activities to enhance teacher professionalism and learning quality. Rendahnya kualitas kinerja guru masih menjadi isu krusial di banyak lembaga pendidikan, khususnya di madrasah ibtidaiyah, di mana supervisi akademik sering kali belum berjalan optimal. Berdasarkan peran sentral kepala madrasah dalam mencapai tujuan pendidikan, penelitian ini bertujuan mengungkap pelaksanaan supervisi akademik untuk meningkatkan kinerja guru. Penelitian menggunakan pendekatan kualitatif dengan teknik wawancara, observasi partisipatif, dan dokumentasi di MI Sirajul Ulum, Probolinggo. Temuan menunjukkan bahwa teknik individual seperti orientasi guru baru, observasi kelas, dan percakapan individual, serta teknik kelompok seperti rapat dewan guru, workshop, buletin board, dan karyawisata telah dilaksanakan namun belum optimal. Hambatan utama adalah kesibukan kepala madrasah karena rapat di luar sekolah dan kurangnya kesiapan sebagian guru untuk disupervisi. Kesimpulannya, supervisi akademik belum berjalan efektif, dan direkomendasikan perlunya kegiatan supervisi yang rutin dan terencana guna meningkatkan profesionalisme guru serta kualitas pembelajaran.